2015
DOI: 10.14202/vetworld.2015.989-993
|View full text |Cite
|
Sign up to set email alerts
|

Association of milk components with intra-mammary inflammation in Jaffrabadi buffaloes

Abstract: Aim:To study the alteration of major milk components such as milk fat, protein, lactose, solid not fat (SNF) and total solids (TS) and their association with different degree of intra-mammary inflammation (IMI) in Jaffrabadi buffaloes.Materials and Methods:Milk samples (n=1516) were collected from Jaffrabadi buffaloes separately from each quarter. Milk samples were analyzed for milk fat, protein, lactose, SNF and TS percent on the same day using milk analyzer “LACTOSCAN.” Milk samples were checked for IMI by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(37 reference statements)
0
1
1
Order By: Relevance
“…Previous study reported lower SNF in milk dairy animals affected with udder infection might be associated with alteration of synthetic activity of glandular epithelial cells or leakage of milk constituents from milk to blood (Bansal et al, 2007). Though, mastitis consistently alters milk lactose in buffaloes (Patbandha et al, 2015), in our study such variation was not observed.…”
Section: Milk Productioncontrasting
confidence: 67%
“…Previous study reported lower SNF in milk dairy animals affected with udder infection might be associated with alteration of synthetic activity of glandular epithelial cells or leakage of milk constituents from milk to blood (Bansal et al, 2007). Though, mastitis consistently alters milk lactose in buffaloes (Patbandha et al, 2015), in our study such variation was not observed.…”
Section: Milk Productioncontrasting
confidence: 67%
“…For example, inadequate machinery maintenance, bad practices, and hasty calf separation can result in delayed milk ejection and/or incomplete emptying of the udder and alveolar compartment (Mota-Rojas et al 2022; Napolitano et al 2022). Moreover, other factors involved could be the lack of proper visual, auditory and tactile stimulation during the milking process, excessive noise, changes in the milking routine that impact the laterality of the female and the concentration of odors in the milking parlor (Thomas et al 2004(Thomas et al , 2005 Positive HAR in the milking parlor, together with good husbandry practices are not only beneficial for the welfare of buffaloes, but also are related to the udder health and prevention of other inflammatory process (Patbandha et al 2015;Gabr et al 2017;Rahman et al 2019).…”
Section: Human-animal Relationship During Milkingmentioning
confidence: 99%
“…The major aim of this study was to investigate the concentrations of airborne microorganisms and to examine the species composition in a vast number of buffalo stables located in Southern Italy. 17…”
Section: Introductionmentioning
confidence: 99%